Spatial and seasonal variations of near-inertial kinetic energy in the upper Ross Sea and the controlling factors - Zhang, Yimin; Yang, Wei; Zhao, Wei; Zhang, Yongli; Shen, Jiawei; Wei, Hao (Frontiers in Marine Science, 2023)
The spatial distribution and seasonal variation of near-inertial kinetic energy (NIKE) in the upper Ross Sea (RS) are examined using the 1/4° NEMO3.6-LIM3 sea ice physical–biological coupled model. The annual-mean surface and mixed layer-integrated NIKE have large values at the shelf break around Iselin Bank and the northeast area outside the continental shelf. The spatial distribution of the surface and mixed layer-integrated NIKE in the austral summer RS is mainly controlled by the near-inertial wind stress magnitude (NIWSM), which acts as the energy source. The northeast high NIKE agrees with the large NIWSM there. Semidiurnal tides only contribute to the NIKE peak around the Iselin Bank and shelf break. The change of mixed layer depth (MLD) can induce spatial discrepancies between surface and mixed layer-integrated NIKE. The shallower MLD in the western RS limits the near-inertial energy in a thin layer, which has induced the large surface NIKE there. The NIKE in the upper RS has a pronounced seasonal variation with the largest surface and mixed layer-integrated NIKE both observed during austral summer. The seasonal variation of NIWSM and sea ice concentration play an important role in inducing the seasonal variation of NIKE. While the NIWSM acts as the main energy source of NIKE, the presence of sea ice can prevent the wind from directly acting on the surface ocean, inducing the low NIKE during austral winter.